2003
DOI: 10.1093/annonc/mdg457
|View full text |Cite
|
Sign up to set email alerts
|

Therapy and survival after recurrence of Ewing’s tumors: the Rizzoli experience in 195 patients treated with adjuvant and neoadjuvant chemotherapy from 1979 to 1997

Abstract: The outcome of Ewing's tumor patients who relapse after combined treatment is very poor. However, these patients may be divided into two groups: those that can be cured with traditional treatments (late relapse and/or only lung metastases), and a second group of patients (early relapses with metastases in lungs and/or other sites) who gain no benefit from traditional therapies. For the latter group, multicenter studies are needed to evaluate new strategies of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
111
4
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 13 publications
13
111
4
3
Order By: Relevance
“…Some tissues had excessive necrosis (Bologna system 2-3) 60 induced by neoadjuvant chemotherapy. 61,62 These same problems have been also described in previous studies. 21,45 Based on the present data, we recommend the use of both RT-PCR and FISH as complementary analyses; had we only used one or the other for each patient, the number of uninformative cases would have been higher.…”
Section: Discussionsupporting
confidence: 83%
“…Some tissues had excessive necrosis (Bologna system 2-3) 60 induced by neoadjuvant chemotherapy. 61,62 These same problems have been also described in previous studies. 21,45 Based on the present data, we recommend the use of both RT-PCR and FISH as complementary analyses; had we only used one or the other for each patient, the number of uninformative cases would have been higher.…”
Section: Discussionsupporting
confidence: 83%
“…Late relapse (≥2 years from the time of original diagnosis), lung-only metastases, local recurrence that can be treated with radical surgery, and intensive chemotherapy are the most favorable prognostic factors, whereas early relapse (<2 years from the time of original diagnosis) with metastases in lungs and/or other sites, recurrence at local and distant sites, elevated LDH level at initial diagnosis, and initial recurrence are considered adverse prognostic factors. [53][54][55][56] In a recent retrospective analysis, site of first relapse and time to first relapse were significant prognostic factors for adult patients with localized Ewing sarcoma. 57 The probability of 5-year postrelapse survival was 50% and 13% for patients with local and distant relapse, respectively.…”
Section: Treating Relapsed/refractory Diseasementioning
confidence: 99%
“…The efflux pumps are identified as ATP-binding cassette (ABC) transporters characterized with their homologous ATPbinding domains, including P-glycoprotein (Pgp), an MDR1 gene product, and multidrug resistance-associated protein 1 (MRP1). 13,14 Because key drugs in chemotherapy for OS and EFTs, including adriamycin (Dox), [15][16][17] are the substrates of Pgp and MRP1, 18 drug resistance in OS and EFTs might be related to these efflux pumps.A recent study demonstrated that FK228 exhibited potent antitumor effects on OS. 19 We have also demonstrated that HDACIs induced p21 expression in EFT cells, which was inhibited by EWS-Fli1 fusion protein, and in addition we showed that the induced p21 led EFT cells to growth arrest at the G1 phase in the cell cycle.…”
mentioning
confidence: 99%
“…The efflux pumps are identified as ATP-binding cassette (ABC) transporters characterized with their homologous ATPbinding domains, including P-glycoprotein (Pgp), an MDR1 gene product, and multidrug resistance-associated protein 1 (MRP1). 13,14 Because key drugs in chemotherapy for OS and EFTs, including adriamycin (Dox), [15][16][17] are the substrates of Pgp and MRP1, 18 drug resistance in OS and EFTs might be related to these efflux pumps.…”
mentioning
confidence: 99%